Depth characterization by confocal raman microscopy of oxygen inhibition in free radical photopolymerization of acrylates: Contribution of the thiol chemistry. Issue 3 (31st October 2012) - Courtecuisse, François; Cerezo, Javier; Croutxé‐Barghorn, Céline; Dietlin, Céline; Allonas, Xavier
Abstract The oxygen inhibition of acrylate photopolymerization using visible light was depth characterized by confocal Raman microscopy. The sample thickness was found to influence the depth conversion profile. With increasing sample thickness, the conversion at the surface was increased and the oxygen‐affected layer (OAL) decreased, up to a limit where the profiles became independent of the thickness. The addition of a thiol in the acrylate mixture reduced the OAL and the conversion in this region increased. This effect was noticeable even at low concentration of thiol. Real‐time infrared spectroscopy (RT‐FTIR) experiments pointed out that for low thiol content, this beneficial effect is not only attributable to the thiol–ene process—oxygen insensitive—but also to the homopolymerization of acrylates which is enhanced. Homopolymerization and thiyl radical addition were found to have the same impact on the overall mechanism. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013